Ortho group activation of a bromopyrrole ester in Suzuki-Miyaura cross-coupling reactions: Application to the synthesis of new microtubule depolymerizing agents with potent cytotoxic activities. Issue 12 (15th June 2017) - Gupton, John T.; Yeudall, Scott; Telang, Nakul; Hoerrner, Megan; Huff, Ellis; Crawford, Evan; Lounsbury, Katie; Kimmel, Michael; Curry, William; Harrison, Andrew; Juekun, Wen; Shimozono, Alex; et al.
Graphical abstract: Abstract: New microtubule depolymerizing agents with potent cytotoxic activities have been prepared with a 5-cyano or 5-oximino group attached to a pyrrole core. The utilization of ortho activation of a bromopyrrole ester to facilitate successful Suzuki-Miyaura cross-coupling reactions was a key aspect of the synthetic methodology. This strategy allows for control of regiochemistry with the attachment of four completely different groups at the 2, 3, 4 and 5 positions of the pyrrole scaffold. Biological evaluations and molecular modeling studies are reported for these examples.